Visitor’s Satisfaction and Community Empowerment for Sustainable Ecotourism: An Evaluative Study on Ecotourism Spots of Uttar Kannada District of Karnataka (India) - Hanumantha, M.; Shahapuramath, Girish B.; Biradar, Prabhugoud; Jagadish, M. R.; Menasinhal, S. K. (Indian Forester, 2019)
The present study was carried out in the selective spots of Uttara Kannada in Western Ghats from June 2014 to May 2015. The study made significant observations regarding the tourism facilities at spot, the problems encountered and satisfaction level of tourists and provided the setting for analyzing the impact of ecotourism in Uttar Kannada and study revealed that ecotourism occupies a significant position in the overall tourism development in this district and has an immense ecotourism potential. High TPI scores relates to higher potential pressure from tourism. Low values for S.C.T R and W are likely to attract tourists to spots as they represent the accessibility and comfort afforded to tourists. In contrast low values for P, R and A have negative effect on potential collision, as each has the potential to reduce tourist motivation to visit spot. Participation of the local communities ensures economic benefits for them, which in the longer run can ensure a better status and an easier life. The study concluded that the ecotourism plays a remarkable role in the overall tourism development and also helps in uplifting the economic conditions of the local people.